A discursivização do local-fronteira no jornalismo: estudo de caso de programas jornalísticos em rádios comunitárias - Zamin, Angela Maria (Universidade do Vale do Rio do Sinos, 2008)
This work investigates the functioning of Journalism in community radios, taking as objects of analysis the journalistic programs Realidade Urgente e Bom Dia Cidade, of the radio stations Nova Aurora FM, from Santana do Livramento, and Elshaday FM, from Uruguaiana, both towns in the state of Rio Grande do Sul. The main concern of this research is the way the “local” is transformed into discourse by this Journalism. The choice, therefore, links community radio to local space. This is a concept of difficult demarcation, which should be related to another spatial magnitude to limit its place, what has made me decide for towns near the geopolitical border as an area of observation and apprehension of the concept of “local”. They are both towns in the state of Rio Grande do Sul: Santana do Livramento, on the border of Uruguai, and Uruguaiana, on the border of Argentina. Moved by the inquietude of trying to understand the concept of “local” in this context, how it is delimited and which senses are attributed to it
Keywords: discurso jornalístico; fronteira; rádio comunitário; jornalismo; border; community radio; journalistic discourse; journalism; Ciências Sociais Aplicadas